The contextual factors in the recognition of commercialization opportunity among Malaysian public universities researchers - Kamisah, Kormin (2012)
Malaysia is striving to achieve the status of a high income and developed nation as envisioned by Vision 2020, where innovation plays an ever-increasing and important role to sustain a rapid rate of economic growth,enhance international competitiveness.The Government has taken various initiatives to support technology commercialization in Malaysian Public Universities such as the allocation of huge funding for Research and Development(R&D)activities. However,besides the huge amount allocated for R&D, the commercialization rate is very low.If this situation is unchecked, then the Government vision for wealth creation would not be achieved.Therefore,the purpose of this study is to observe the capability of the researchers in the recognition of commercialization opportunity.This study also aims to determine the contextual factors that could influence a researcher’s capability in the recognition of commercialization opportunity.Online questionnaires were sent to 400 respondents among Malaysian Public Universities’ researchers in the field of Science and Technology.The questionnaires covered elements such as knowledge, researcher’s behavior, social network and university support.Of 400 respondents,101 complete responses were received and analyzed.This study identified that knowledge,researcher’s behavior and social network are factors required to recognize the commercialization opportunity successfully.This study has indicated that the Malaysian Public universities’ researchers possess greater technological knowledge, knowledge of the customer, knowledge of the government’s rules and regulations and knowledge of the customer’s problems.The researchers were found to be creative in R&D and proactively search information related to their R&D fields.Most of the researchers also believed that commercialization of their technology are their strongest motive in R&D activities.Results of this study also indicated that the researchers possess moderate capability in the knowledge of the competitor,knowledge of costing, informal interaction with industries,supplier, involvement of multidisciplinary research team and participation in professional forums.However,the researchers were found to have poor capability in formal interaction with industries and with mentors. Researcher’s level of education,industrial work experience and university support were found to play as a moderator that strengthen the relationship between knowledge, researcher’s behavior,social network and the recognition of commercialization opportunity.